The phenomenology of deep brain stimulation-induced changes in OCD: an enactive affordance-based model - de Haan, Sanneke; Rietveld, Erik; Stokhof, Martin; Denys, Damiaan (Frontiers in Human Neuroscience, 2013)
People suffering from Obsessive-Compulsive Disorder (OCD) do things they do not want to do, and/or they think things they do not want to think. In about 10% of OCD patients, none of the available treatment options is effective. A small group of these patients is currently being treated with deep brain stimulation (DBS). DBS involves the implantation of electrodes in the brain. These electrodes give a continuous electrical pulse to the brain area in which they are implanted. It turns out that patients may experience profound changes as a result of DBS treatment. It is not just the symptoms that change; patients rather seem to experience a different way of being in the world. These global effects are insufficiently captured by traditional psychiatric scales, which mainly consist of behavioral measures of the severity of the symptoms. In this article we aim to capture the changes in the patients' phenomenology and make sense of the broad range of changes they report. For that we introduce an enactive, affordance-based model that fleshes out the dynamic interactions between person and world in four aspects. The first aspect is the patients' experience of the world. We propose to specify the patients' world in terms of a field of affordances, with the three dimensions of broadness of scope (“width” of the field), temporal horizon (“depth”), and relevance of the perceived affordances (“height”). The second aspect is the person-side of the interaction, that is, the patients' self-experience, notably their moods and feelings. Thirdly, we point to the different characteristics of the way in which patients relate to the world. And lastly, the existential stance refers to the stance that patients take toward the changes they experience: the second-order evaluative relation to their interactions and themselves. With our model we intend to specify the notion of being in the world in order to do justice to the phenomenological effects of DBS treatment.